Committee Opinion No. 670: Immediate Postpartum Long-Acting Reversible Contraception. Issue 2 (August 2016) - N/A,
Abstract : ABSTRACT: Immediate postpartum long-acting reversible contraception (LARC) has the potential to reduce unintended and short-interval pregnancy. Women should be counseled about all forms of postpartum contraception in a context that allows informed decision making. Immediate postpartum LARC should be offered as an effective option for postpartum contraception; there are few contraindications to postpartum intrauterine devices and implants. Obstetrician–gynecologists and other obstetric care providers should discuss LARC during the antepartum period and counsel all pregnant women about options for immediate postpartum initiation. Education and institutional protocols are needed to raise clinician awareness and to improve access to immediate postpartum LARC insertion. Obstetrician–gynecologists and other obstetric care providers should incorporate immediate postpartum LARC into their practices, counsel women appropriately about advantages and risks, and advocate for institutional and payment policy changes to support provision.